Profiles of Physical Activity and Competence in Children: Associations With Bullying and Peer Context in the Classroom (Baltic Journal of Sport and Health Sciences, 2026)
Physical activity and motor competence are not only critical for children’s physical health but are also associated with social integration and emotional wellbeing. Children who are physically competent and engaged in regular physical activity are often perceived more positively by their peers, while those with lower activity levels or motor skills may experience social exclusion or bullying. This study explores how profiles based on cardiorespiratory fitness, motor competence, perceived sport and physical competence, and device-measured physical activity relate to bullying experiences and the perceived classroom peer context (CRPC).This cross-sectional study aimed to create profiles based on cardiorespiratory fitness, motor competence, perceived sport and physical competence, and device-measured physical activity, and to examine their association with being bullied and perceived CRPC. All variables were assessed in 339 Finnish schoolchildren. Latent profile analysis was used to identify the profiles. Regression models were employed to analyse the likelihood of being bullied and ANOVA was conducted to examine the differences in CRPC across the profilesThree profiles were identified: highly physically active and competent, moderately physically active and competent, and poorly physically active and competent. Children in the poorly physically active and competent profile were 3.8 times more likely to be bullied than children in the highly physically active and competent profile, and 2.2 times more likely to be bullied than children in the moderately physically active and competent profile. Also, children in poorly physically active and competent profile reported the lowest levels of peer acceptance and social support.This study highlights the significant role of physical activity and competence profiles in shaping children’s experiences with bullying, social support, and peer acceptance. Children with lower physical activity and competence were most likely to be bullied and reported the lowest levels of peer acceptance and social support. These findings underscore the importance of fostering an inclusive and supportive peer environment, as well as encouraging physical activity in children, to enhance both their physical wellbeing and social integration within the classroom.Support/Funding Source: Academy of Finland: The Strategic Research Council.